Zebrafish Models for Human Skeletal Disorders - Marí-Beffa, Manuel; Mesa-Román, Ana B.; Duran, Ivan (Frontiers in Genetics, 2021)
During recent years, zebrafish has emerged as an interesting model species to evaluate chemical treatments against human skeletal dysplasia. Due to its versatility and low cost of experiments, zebrafish models are now available to analyze the genetic and developmental bases of about 100 human skeletal dysplasia. This offer is also complementary to mammalian models in the search for therapeutic drugs against diseases such as osteogenesis imperfecta, skeletal ciliopathies, dwarfisms, dysostoses or osteopetrosis related disorders among many other skeletal dysplasias. In this article, we review the state-of-art of this “aquarium to bedside” approach and the expected venues that arise from these studies.